PWE-026 Elucidating the pathogenic potential of the intestinal pathogen campylobacter showae. (17th June 2017) - Gemmell, M; Hsu, T; Berry, SH; Mukhopadhya, I; Hansen, R; Michaud, M; El-Omar, EM; Nielsen, HL; Nielsen, H; Huttenhower, C; Garrett, W; Hold, GL
Abstract : Introduction: In recent years, an increasing number of Campylobacter species have been associated with human gastrointestinal diseases. Campylobacter showae, an oral commensal that was historically linked to gingivitis and periodontitis, has recently been associated with newly diagnosed and established inflammatory bowel disease, hepatolithiasis, and colorectal cancer. The aim of this study was to generate robust genome sequence data for a number of clinical C. showae strains and identify functional properties that could explain their pathogenic potential. Method: Genomes of eight C. showae strains were sequenced, assembled, annotated and compared including four strains from paediatric Crohn's disease patients, three strains from colonic adenomas and one from a gastroenteritis patient. A series of functional analyses were also undertaken including adhesion and invasion assays, toxicity assays and inflammatory cytokine production assessment. Results: The 8 new genome assemblies were of high contiguity and completeness and compared favourably with the existing 3 C . showae genomes. Functional analysis indicated that colonic strains could be classified into 2 groups - adherent/invasive vs non-adherent strains with differing virulence factors between the groups, which may be explained by specific genes. Overall, the 11 strains contained 4591 unique gene centroids. Adherent/invasive strains had 807 unique centroids, while non-adherent/non-invasive strains had 497 unique centroids (in 2 or more strains). The oral strain – RM3277 also contained 270 centroids not shared with the colonic strains. Adherent strains possessed a number of bacterial secretion system proteins including Type I and IV machinery that were absent in non-adherent strains. These differences may contribute to the distinct phenotypes observed between strains relating to motility, metal ion transport and host cell interaction. All strains contained unique plasmid sequences as well as a number of predicted genomic islands including some prophage clusters. Conclusion: Our findings indicate that C. showae strains are phenotypically and genetically diverse, and suggest the genomes of this bacterium contain modifications in secretion systems that may play an important role in their virulence potential. Additionally, we have greatly added to the current C. showae resources with genome and plasmid assemblies of 8 strains. Disclosure of Interest: None Declared